2022
DOI: 10.21203/rs.3.rs-1368555/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Feasibility and acceptability of a multicomponent, group psychological intervention for adolescents with psychosocial distress in public schools of Pakistan: A feasibility cluster randomized controlled trial (cRCT)

Abstract: Background Child and adolescent mental health problems are a global public mental health priority. However, there is a lack of evidence-based scalable psychological interventions for adolescents living in low resource settings. This trial was designed to evaluate the feasibility and acceptability of delivering the World Health Organization’s Early Adolescent Skills for Emotions (EASE) intervention at public schools in a rural sub-district in Rawalpindi, Pakistan. Methods A two arm, single blinded, feasibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…All outcome measures have been translated in Urdu and adapted to suit the local cultural context as part of the associated feasibility study (trial registration NCT04254393). 12 …”
Section: Methods and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…All outcome measures have been translated in Urdu and adapted to suit the local cultural context as part of the associated feasibility study (trial registration NCT04254393). 12 …”
Section: Methods and Analysismentioning
confidence: 99%
“…EASE has been previously translated in Urdu (National Language of Pakistan), culturally adapted for implementation in public schools and feasibility tested in eight public schools of rural Pakistan using a feasibility cluster randomised controlled trial (cRCT) design (trial registration NCT04254393). The results of the evaluation demonstrated the acceptability and feasibility of the adapted intervention to be delivered by non-specialist facilitators in public school settings of Pakistan and exhibited promising effects on improving adolescent’s well-being 12…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In order to solve youth unemployment in Pakistan, focused initiatives that address the root causes of unemployment and provide young people with long-term work prospects are required. A comprehensive policy framework is proposed by Hamdani et al (2022) that includes actions to increase labor market flexibility, encourage entrepreneurship and innovation, and improve access to education and skill training. Furthermore, in order to guarantee that all young people have fair access to employment prospects, Javed et al, (2022) stress the significance of tackling structural hurdles and inequities in the labor market, such as gender discrimination and geographical discrepancies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…1 in 4 adolescent goes through mental health issues that require immediate attention. 1 It is also well documented that many mental health disorders emerge in late childhood and early adolescence and they exacerbate to the burden of these disorders in youth and later in life. 2 In severe cases of anxiety and depression sufferer may commit suicide, it is reported that every 40 seconds one person dies of suicide.…”
Section: Lubna Ghazalmentioning
confidence: 99%